Mrs Implications of Reading the Qur’ān with an Elaboration Approach to Older Adult’s Memory - Multahada, Erna (Jurnal Studi Al-Qur'an, 2023)
This study aims to determine the implications of reading the Al-Qur’ān with an elaboration approach to older adult memory. Participant N = 42 (aged 55-78 years). Participants were obtained using a purposive technique at the Majlis Ta’lim X. This study uses a quasi-experimental approach with a discontinuity regression design. Reading the Al-Qur’ān with an elaboration approach is used to 1) understand the meaning of the verses of the Al-Qur’ān and 2) learn the science of Tahsin and tajwid. The al-Qur’ān reading questionnaire using interactive theory was made to find the implications of reading Al-Qur’ān with elaboration and memory questionnaires applying two-factor theory and recognition. The study results show implications for reading the Al-Qur’ān with an elaboration approach to late adult memory at Majlis Ta’lim X. In conclusion, there are implications for reading the Al-Qur’ān with an elaboration approach to late adult memory at Majlis Ta’lim X.